2022
DOI: 10.1039/d1fo03398k
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of sulforaphane in intestinal inflammation: a review

Abstract: Intestinal inflammation represented by inflammatory bowel disease (IBD) has become a global epidemic disease and the number of patients is still increasing. This digestive tract disease not only affects the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 119 publications
0
18
0
Order By: Relevance
“…Sulforaphane (Sfn), an aliphatic isothiocyanate found as a glucosinolate precursor in cruciferous vegetables, is highly investigated in the context of cancer prevention and inflammation-related disorders, including psoriasis, inflammatory bowel disease, neurodegeneration, or atherosclerosis (e.g., 8 13 ). Numerous in vitro and in vivo studies revealed the ubiquitin ligase adapter Keap1 as one of Sfn’s main targets ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sulforaphane (Sfn), an aliphatic isothiocyanate found as a glucosinolate precursor in cruciferous vegetables, is highly investigated in the context of cancer prevention and inflammation-related disorders, including psoriasis, inflammatory bowel disease, neurodegeneration, or atherosclerosis (e.g., 8 13 ). Numerous in vitro and in vivo studies revealed the ubiquitin ligase adapter Keap1 as one of Sfn’s main targets ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…This metabolite has been broadly characterized revealing cutting edge information on its health benefits, specifically related to preventing the onset of diverse types of cancer [ 44 ], in addition to key physiological activities, such as anti-depressant/anxiolytic-like effects, hypoglycemic, and anti-inflammatory activities [ 45 , 46 , 47 ]. Related to the latter activity and closely related to the concentration of dietary SFN reached in the upper intestinal sections, SFN has been recently related to the prevention of the severity of intestinal bowel disease, an emerging epidemic disorder that needs new therapeutic agents contributing to lower the incidence and severity of the clinical symptoms [ 48 ]. In this frame, the current study showed that although all materials digested after processing by lyophilisation, low-temperature, and decreasing temperature gradient drying experienced an augment of the SFN concentration in the digestion process, the highest values were for broccoli stalk’s core independently of the treatment applied, achieving concentrations of 3.8–4.1 g/kg dw ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of CPZ-intoxicated rats with SF counteracted the enhanced oxidative stress in both cardiac and hepatic tissues. SF exhibited the potential to enhance the expression of detoxification or defensive enzymes via the Keap1/Nrf2/ARE signaling pathway [ 30 ]. Immunohistochemical results demonstrated Nrf-2 activation upon treatment with SF; this could be ascribed to the potential of Nrf-2 to regulate the up-regulation of detoxification genes to activate a cytoprotective response, through mediating the inactivation of oxidants and favoring the synthesis of antioxidants [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf-2 is vital for the maintenance of redox signaling in response to stress [ 71 ]. Under stress conditions such as CPZ-induced toxicity, Nrf-2 loses its DNA binding to ARE, however, this loss of Nrf-2/ARE binding could be reversed by using “Nrf-2 agonists” such as SF [ 72 , 73 ]; suggesting that Nrf-2-mediated survival pathways are reversible and responsive by using effective agonists of Nrf-2 such as SF, which act as “indirect antioxidant” with anti-inflammatory potential [ 30 , 74 ]. The inhibitory potential of SF on abnormally activated inflammation is related to the activation of Nrf-2-mediated signaling pathways [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation